IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 SARUDU DALAM MENINGKATKAN PEMBELAJARAN - Rahman, Mujibu (Katalogis, 2016)
This study aims to identify and describe the Policy Implementation Unit Level Curriculum (SBC) in improving learning in SMK Negeri 1 Sarudu. This research is a qualitative descriptive study with a study population of 16 people, .Teknik data collection using observation, interview and documentation study. The data analysis technique used is descriptive qualitative. The results showed that the policy implementation Unit Level Curriculum (SBC) at SMK 1Sarudu based on the theory of Edward III, which include: Communication, Resources, disposition and bureaucratic structure in SMK 1 Sarudu suboptimal even though the policy implementation of SBC is in conformity with the standards of competence / basic competence but there are some programs that are not performing well as the development program or department areas of expertise, competence test execution and implementation of learning programs. Factors affecting less optimal for policy implementation level curriculum, among others, limited education facilities / infrastructure and support available budget and human resources seen from Aspe kkualitas and quantity